Food ordering system using IPad - Abdul Hadi, Abdul Ghani (2012)
Food Ordering System (FOS) using iPad is a management system that helps ordering in restaurants or any food business that has ordering services.The system implements the concept of electronic menus by using iPad tablet as a platform. Beautiful interface and easy to understand is the main strength of the application.The system is operated online where the data connection is done by the web services. Features of this system is location detection that help customers find the restaurants,table status that help customer to check the availability of the table,menus with picture,price and time to cook that help customer understand more about the dishes and how long should he or she wait. The manager can use the system to manage the menus.Disable the food if the supply no longer enough to make it.Manage the order without seeing the customer face by face.With this system waiter no longer needed to take an order.Customer directly order to the system and chef or cook can see the order on the kitchen directly.Order is now easy.